en - Dewi, Komang Ayu Rosmala; Sedeng, I Nyoman; Soethama, Putu Lirishati (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 28 No 2 (2021) : September, 2021)
This article discussed about morphosyntax that deals with the combination of morphology and syntax. The article was aimed to find out the derivational suffixes forming adjectives and the syntactic functions of the adjectives found in the data source. The data of this article were taken by library research method and note-taking technique from the novel Forrest Gump, which published in 157 pages and 26 chapters by Pocket Books in 1994. This novel is written by Winston Groom. The collected data were analyzed descriptive qualitatively based on the theory of Morphology and Syntax by Quirk, et al (1985). This article revealed that there were the attachment of suffix {-ful}, {-less}, {-ly}, {-y}, {-al}, {-ial}, {-ic} and {-ous} changed the base noun into adjective, it is called denominal adjectives . Then, deverbal adjectives which made the word class changed from verb into adjective, there were the attachment of suffix {-able} and    {-ive}. Meanwhile, for the syntactic functions there were three types found, they are attributive, predicative and postpositive.